The Effect of Service Quality, Store Atmosphere, and Brand Image on Customer Loyalty in the Jakarta Local Coffee Shop - Afyani, Nabilla Putri; Gunawan, Freddy; Soesetyo, Suwandy; Mustikasari, Faranita (Review of Management and Entrepreneurship, 2023)
This study investigates the relationship between service quality, store atmosphere and brand image towards customer loyalty by considering customer satisfaction as a mediator. Data collection was carried out on 180 Jakarta residents who regularly visit local coffee shops in Jakarta. The results reveal that service quality, store atmosphere and brand image has a significant effect on customer satisfaction, then store atmosphere and customer satisfaction has a significant effect on customer loyalty. On the other hand, service quality and brand image have no effect on customer loyalty. By having service quality as expected, a unique store atmosphere and a good brand image, it will trigger customers to at least try to choose and come to the coffee shop. So in the end, this study is expected to be able to develop customer satisfaction and create loyal customers to local coffee shops in Jakarta.